A novel Drosophila model of TDP-43 proteinopathies: N-terminal sequences combined with the Q/N domain induce protein functional loss and locomotion defects - Simona Langellotti; Valentina Romano; Giulia Romano; Raffaella Klima; Fabian Feiguin; Lucia Cragnaz; Maurizio Romano; Francisco E. Baralle (The Company of Biologists, 2016)
Transactive response DNA-binding protein 43 kDa (TDP-43, also known as TBPH in Drosophila melanogaster and TARDBP in mammals) is the main protein component of the pathological inclusions observed in neurons of patients affected by different neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS) and fronto-temporal lobar degeneration (FTLD). The number of studies investigating the molecular mechanisms underlying neurodegeneration is constantly growing; however, the role played by TDP-43 in disease onset and progression is still unclear. A fundamental shortcoming that hampers progress is the lack of animal models showing aggregation of TDP-43 without overexpression. In this manuscript, we have extended our cellular model of aggregation to a transgenic Drosophila line. Our fly model is not based on the overexpression of a wild-type TDP-43 transgene. By contrast, we engineered a construct that includes only the specific TDP-43 amino acid sequences necessary to trigger aggregate formation and capable of trapping endogenous Drosophila TDP-43 into a non-functional insoluble form. Importantly, the resulting recombinant product lacks functional RNA recognition motifs (RRMs) and, thus, does not have specific TDP-43-physiological functions (i.e. splicing regulation ability) that might affect the animal phenotype per se. This novel Drosophila model exhibits an evident degenerative phenotype with reduced lifespan and early locomotion defects. Additionally, we show that important proteins involved in neuromuscular junction function, such as syntaxin (SYX), decrease their levels as a consequence of TDP-43 loss of function implying that the degenerative phenotype is a consequence of TDP-43 sequestration into the aggregates. Our data lend further support to the role of TDP-43 loss-of-function in the pathogenesis of neurodegenerative disorders. The novel transgenic Drosophila model presented in this study will help to gain further insight into the molecular mechanisms underlying neurodegeneration and will provide a valuable system to test potential therapeutic agents to counteract disease.